Results after 10 years of colorectal cancer screenings in Spain: Hospital incidence and in-hospital mortality (2011–2016) - Darbà, Josep (PLoS One, 2020)
BACKGROUND: Colorectal cancer incidence in Spain increased considerably between the early nineties and 2010. To reverse this tendency, screenings were progressively implemented starting the year 2001, targeting the population aged 50 to 69 years. OBJECTIVES: This study aimed to update colorectal cancer incidence and mortality trends in Spain and provide a detailed analysis of disease management and risk factors involved in in-hospital mortality. METHODS: To this aim, anonymised primary and specialised care admission records from 2011 to 2016 were extracted from a Spanish claims database representative of all Spanish regions. RESULTS: Primary care files from 37,317 patients and specialised care files from 192,048 patients were obtained, in which males represented the 56.17% and 60.70% of patients respectively. In-hospital mortality rate was 10.07% and remained stable during the study period, similarly to colorectal cancer incidence within the hospitalised population, which was 106 per 10,000 patients. Patients deceased during the hospitalisation presented an increased presence of metastatic tumours. Mean length of hospital stay decreased significantly over the study period from 13.43 days to 11.67 days (p<0.001), similarly to patients’ 30-day readmission rate, which registered a decrease from the 15.29% to 13.58% (p<0.001). In consequence, the direct medical cost measured per patient, of €10,992, decreased over time. The implementation of colorectal cancer screening programmes caused a significant decrease in the number of new diagnoses in patients aged 75 to 79 years that may be attributable to the implementation of colorectal cancer screening programmes; however, in-hospital mortality was not reduced. Metastatic tumours and other conditions as anaemia are associated with higher in-hospital mortality rates.